Effects of starvation on serum levels of calcium, phosphorus, uric acid and creatinine in newly hatched broiler chicks - AL-RAWASHDEH, O F; LAFI, S Q; ABDUL-AZIZ, T A; HAILAT, N Q; EREIFEJ, K I (The Indian Journal of Animal Sciences, 2013)
Newly hatched broiler chicks were starved for 1-5 days and their serum levels of calcium, phosphorus, uric acid and creatinine, and body weight, were assessed and compared te their counterparts in fed chicks. A slight and steady decrease in the mean calcium level and a significant decrease (P<0.05) in the mean phosphorus level in the serum of fasted group compared to the fed group were. observed. A significant increase in the mean values of uric acid (p<0.05) and a substantial increase in the mean values of creatinine were also observed from the second and third days onward of fasting respectively. There was a significant negative correlation between uric aCId and body weigh-(r = -0.468). and between uric acid and calcium (r = -0.232).